Pola Penerapan Sistem ‘ngabdi’ yang Dilakukan Pondok Pesantren Bahrul Maghfiroh Malang dalam Konteks Manajemen Sumber Daya Manusia - Bambang Septiawan; Muhammad Adib Mawardi; Muhammad Rizal (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
This study aims to analyze the pattern of implementing the 'ngabdi' system applied to the Bahrul Mahfiroh Islamic Boarding School in the context of HRM. This research is actually focused on the development of human resources in the Islamic boarding school Bahrul Maghfiroh Malang. This is very interesting because there is an integration between pesantren culture and HRM theory which is carried out in the economic and business spheres. In addition, acculturation of human resource development theory and Islamic boarding school culture is also discussed in this study. One of the ways to serve the pesantren is to increase the quality of the output of the students. The method used is a qualitative approach and is included in the descriptive scope because it describes the phenomena that occur in this study. The Miles and Huberman approach model is adopted for the data analysis technique performed. The results prove that 'ngabdi' also applies the HRM theory even though several factors are acculturated with the wisdom of the pesantren itself. In general, the implementation pattern of service in Bahrul Maghfiroh applies the HRM theory starting from recruitment, training, compensation, and termination of employment, although there are modifications according to the needs of the pesantren